Genetic diversity of Indigofera kirilowii Maxim. ex Palibin using AFLP makers - Wu, Qikui; Sun, Limin; Liu, Xiaojing; Wang, Xuan; Sun, Xia; Xing, Shiyan (Bangladesh Journal of Botany, 2019)
The present studies were conducted to assess the genetic diversity and to infer population structure of 220 individuals of Indigofera kirilowii from 8 natural populations of Shandong province, north China, using amplified fragment length polymorphism (AFLP) markers. A total of 1589 AFLP bands were produced, of which 99.87% were polymorphic. High genetic diversity was considered (H = 0.1401; I = 0.2346), with high genetic differentiation (GST = 0.1058), while estimates of gene flow (Nm) were high in all analysis. No correlations were observed between geographic location and genetic diversity (r = –0.0901; p = 0.3293). Based on the results, here a strategy for the conservation of I. kirilowii germplasm was proposed.